On Bellamy’s Set Function Γ - Macías, Sergio (Topology Proceedings, 2020)
David P. Bellamy defined a set function Γ in his paper Some topics in modern continua theory [Continua, Decompositions, Manifolds, Austin, TX: University of Texas Press, 1983, 126]. We investigate this set function and prove his conjecture.